Orf132: a critical gene for LSDV replication and its role in Er stress-related apoptosis - Yongtao Wang; Shiwei Zhang; Hailing Li; Yali Feng; Ying Zhang (Virology Journal)
Abstract Lumpy skin disease (LSD), caused by the lumpy skin disease virus (LSDV), is an emerging infectious disease in China that primarily affects cattle. LSDV and goatpox virus (GTPV) belong to the Capripoxvirus genus and exhibit high genomic homology, enabling cross-immunogenicity. Comparative genome analysis revealed that LSDV contains a unique gene, Orf132, whose function remains uncharacterized. In this study, we first confirmed that the recombinant ORF132 protein exhibits immunoreactivity against sera from LSDV-infected cattle. To investigate the biological role of Orf132, we generated an Orf132 deletion strain (LSDV-ΔOrf132). Compared with the wild-type LSDV, the replication capacity of LSDV-ΔOrf132 was reduced approximately tenfold, indicating that Orf132 is critical for viral replication. Transcriptomic analysis of infected MDBK cells revealed significant alterations in endoplasmic reticulum (ER) protein processing and unfolded protein response (UPR) pathways following Orf132 deletion. qRT-PCR validation showed marked upregulation of ER stress markers, including Grp78, Chop, and Gadd34. Subsequent apoptosis assays established that Orf132 deletion triggers CHOP-Caspase-12-mediated apoptotic pathways. This dysregulated stress response cascade culminates in premature apoptotic scenarios, possibly weakening viral replication. We also showed that adding ORF132 protein effectively inhibited ER stress in LSDV-ΔOrf132-infected cells and rescued the attenuation phenotype of LSDV-ΔOrf132. Our findings collectively revealed that Orf132 is a critical gene for LSDV replication and a negative regulator of ER stress. It plays an essential role in the virus’s life cycle, and its deletion significantly impairs viral replication while inducing ER stress-related apoptosis.